(untitled) (TAMADDUN NURI JURNALI, 2024)
In the modern era, scientific research and innovation are recognized as crucial drivers of progress across all spheres of society. They not only establish new sectors of the economy and improve production efficiency but also address pressing social, cultural, and environmental issues. Innovation integrates new ideas, technologies, and methods to meet societal and market needs. This article explores the essential components of innovation, including the development of new ideas, enhancement of existing processes, and their practical application. The interconnectedness of scientific research and innovation highlights their significance in resolving global challenges, fostering sustainable development, and enhancing social well-being.